Nicotinamide phosphoribosyltransferase and intra-amniotic inflammation in preterm prelabor rupture of membranes - Musilova, Ivana; Kolackova, Martina; Andrys, Ctirad; Drahosova, Marcela; Baranová, Ivana; Chmelarova, Marcela; Stranik, Jaroslav; Jacobsson, Bo; Kacerovsky, Marian (The journal of maternal-fetal & neonatal medicine, 2021)
Introduction: The amniotic fluid nicotinamide phosphoribosyltransferase (NAMPT) levels have not been compared among women with preterm prelabor rupture of membranes (PPROM) comorbid with intra-amniotic infection, sterile intra-amniotic inflammation (IAI), colonization, or without IAI and microbial invasion of the amniotic cavity (MIAC). Therefore, the main aim was to quantify the amniotic fluid NAMPT in women with PPROM complicated by intra-amniotic infection, sterile IAI, or colonization. The second aim was to characterize the diagnostic indices of NAMPT to reveal IAI. The third aim was to determine whether the cervical fluid and maternal serum NAMPT quantitation might be of value in the identification of intra-amniotic inflammatory complications in PPROM.Methods of study: NAMPT levels in amniotic fluid, cervical fluid, and maternal serum were assessed in three independent cohorts of women with singleton pregnancies complicated by PPROM between 24+0 and 36+6 weeks of gestation consisting of 88, 121, and 88 women, respectively. Amniotic fluid samples were obtained by transabdominal amniocentesis, cervical fluid samples were obtained using a Dacron polyester swab and maternal blood was obtained by venipuncture of the cubital vein. The NAMPT levels were measured by an enzyme-linked immunosorbent assay. Testing for MIAC and IAI was performed on all women, who were then categorized into four subgroups: intra-amniotic infection (MIAC and IAI), sterile IAI (IAI alone), colonization (MIAC alone), and without MIAC and IAI.Results: Women with intra-amniotic infection and women with sterile IAI had higher NAMPT levels than did women with colonization and women without MIAC and IAI (intra-amniotic infection: median 73.6 ng/mL, sterile IAI: median 55.5 ng/mL, colonization: median 12.1 ng/mL, without MIAC and IAI: 10.6 ng/mL; p < .0001). An amniotic fluid NAMPT level of 37 ng/mL was the best value for the detection of intra-amniotic infection in women with PPROM. Cervical fluid (p = .51) and maternal serum (p = .50) NAMPT levels did not reflect intra-amniotic inflammatory complications in women with PPROM.Conclusions: Intra-amniotic infection and sterile IAI are associated with higher NAMPT levels in amniotic fluid but not in cervical fluid or maternal serum in women with PPROM. Amniotic fluid NAMPT might be a marker for invasive identification of IAI in PPROM.
Keywords: serum; předčasný odtok plodové vody; plodová voda; Inflammation; gestační stáří; Chorioamnionitis; Gestational Age; Pregnancy; pre-B-cell colony-enhancing factor; těhotenství; visfatin; zánět; Fetal Membranes, Premature Rupture; novorozenec; Amniotic Fluid; chorioamnionitida; lidé; cervical fluid; ženské pohlaví; Humans; Nicotinamide Phosphoribosyltransferase; Infant, Newborn; Amniotic fluid; intra-amniotic inflammation; Female; nikotinamidfosforibosyltransferasa; intra-amniotic infection